Committee Structure and its Implications for Monetary Policy Decision-making - Jan Marc Berk; Beata K. Bierut (Tinbergen Institute, 2003)
We investigate the implications for the setting of interest rateswhen monetary policy decisions are taken by a committee, in whicha subset of members may meet prior to the voting in the committeeand therefore has the possibility to reach consensus ex ante to voteunanimously ex post. We allow for different committee sizes, variousvoting rules and differences in skills among committee members. Wefind that the size of the committee is much less important in deter-mining the degree of interest rate inertia than the skills of committeemembers. Moreover, prior interaction of a subgroup only has a minoreffect on the setting of interest rates by the committee, provided thatmembers on average are equally skilled and voting takes place using asimple majority rule. If either of those assumptions are relaxed, priorinteraction has substantial effects on the setting of interest rates. Inaddition, prior interaction increases the optimal size of the Committee,ceteris paribus.
Keywords: E52; E58; 330; monetary policy; interest rates; voting.; Geldpolitik; Zinspolitik; Abstimmungsregel; Theorie